Crystal structures of the SARS‐CoV‐2 nucleocapsid protein C‐terminal domain and development of nucleocapsid‐targeting nanobodies. (30th October 2021) - Jia, Zhenghu; Liu, Chen; Chen, Yuewen; Jiang, Heng; Wang, Zijing; Yao, Jialu; Yang, Jie; Zhu, Jiaxing; Zhang, Boqing; Yuchi, Zhiguang
Abstract : The ongoing outbreak of COVID‐19 caused by SARS‐CoV‐2 has resulted in a serious public health threat globally. Nucleocapsid protein is a major structural protein of SARS‐CoV‐2 that plays important roles in the viral RNA packing, replication, assembly, and infection. Here, we report two crystal structures of nucleocapsid protein C‐terminal domain (CTD) at resolutions of 2.0 Å and 3.1 Å, respectively. These two structures, crystallized under different conditions, contain 2 and 12 CTDs in asymmetric unit, respectively. Interestingly, despite different crystal packing, both structures show a similar dimeric form as the smallest unit, consistent with its solution form measured by the size‐exclusion chromatography, suggesting an important role of CTD in the dimerization of nucleocapsid proteins. By analyzing the surface charge distribution, we identified a stretch of positively charged residues between Lys257 and Arg262 that are involved in RNA‐binding. Through screening a single‐domain antibodies (sdAbs) library, we identified four sdAbs targeting different regions of nucleocapsid protein with high affinities that have future potential to be used in viral detection and therapeutic purposes. Abstract : Through screening a naive single‐domain antibodies (sdAbs) library, we identified several sdAbs targeting different regions of the nucleocapsid (N) protein of SARS‐CoV‐2. Using X‐ray crystallography and biophysical methods, we revealed the structures of C‐terminal domain (CTD) of N‐protein and characterized its interactions with the identified sdAbs.